Development of biosafety equipment for high containment laboratory and for personal protection in China - Zongxing Zhang; Jinhui Wu; Limei Hao; Ying Yi; Jiancheng Qi (Elsevier, 2020)
Biosafety equipment is the key barrier enabling high containment laboratories to handle high risk agents that may cause serious and potentially lethal infections. This perspective thoroughly analyzes the development of many kinds of key biosafety technologies, and equipment for protection of laboratory workers and for high containment laboratory facilities in China. Over more than ten years of rapid development, China has had remarkable achievements in key biosafety technologies and equipment in high containment laboratories. These technologies basically meet the needs of high containment laboratories construction in China. Furthermore, according to the current global situation regarding the prevention and control of infectious diseases and the technical development level of biosafety equipment, this paper proposes targeted suggestions and notes that China still needs to increase investment in scientific research to provide further technical and equipment support enabling us to build a community with a bright future in terms of human biosafety.